Management accounting change: ABC adoption and implementation - Fadzil, Faudziah Hanim; Rababah, Abedalqader (Vol. 2012 (2012), 2012)
The current research tries to contribute to the successful design and implementation of ABC in the context of Jordanian Manufacturing Companies. In order to satisfy the research objectives, both quantitative and qualitative data are gathered. For the quantitative data, a questionnaire survey was developed for the determination of the present scenario involving ABC adoption and implementation.For the qualitative one, semi-structured interviews were utilized to find out the factors impacting the adoption and implementation of ABC.Data analysis included within company and cross-company analysis. ABC’s adoption and implementation rate were determined through the use of three criteria; namely, adopters, implementers and users or implementers.The primary findings revealed that ABC implementation in the context of Jordanian Manufacturing Companies is approximately 19.5% measured according to the third criteria which is implementers or users.Findings from the semi-structured interviews reveal that factors including fashion, forced decision, fad and efficiency are directly related to ABC implementation decision in the target companies. In addition, factors that both facilitate and motivate ABC implementation are: top management support, non-accounting ownership, higher information technology, education, globalization of consumer, increased competition, growing costs, allocation problems, inability of the traditional cost systems to provide relevant information in the new environment and financial crisis. The findings from the interviews also revealed that the barriers to ABC implementation are associated to behavioral and technical problems.